Oro-facial pain in the community: prevalence and associated impact - Macfarlane TV, Blinkhorn AS, Davies RM, Kincey J, Worthington HV (Blackwell Synergy, 2002)
To determine the prevalence of oro-facial pain (OFP) in the population and within-population subgroups and to describe the associated disability.